2004
DOI: 10.1055/s-2004-820933
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation Inhibits the Interaction of 14‐3‐3 Proteins with the Plant Plasma Membrane H+‐ATPase

Abstract: Interaction of 14-3-3 proteins with their targets depends not only on the phosphorylation status of the target but also on that of 14-3-3 (Fu et al., 2000). In this work we demonstrated that the maize 14-3-3 isoform GF14-6 is a substrate of the tyrosine kinase insulin growth factor receptor 1. By means of site-directed mutants of GF14-6, we identified Tyr-137 as the specific tyrosine residue phosphorylated by the insulin growth factor receptor 1. Phosphorylation of GF14-6 on Tyr-137 lowered its affinity for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…These data also suggest that these epitopes maintain the same structural conformation regardless of the client-binding state. Also of interest is the fact that GBC mAb 5D6 epitope in loop 6 is in the same region that has been recognized as the site of Ser phosphorylation in mammalian 14-3-3s (Woodcock et al, 2003) and potential Tyr phosphorylation in plant 14-3-3s (Giacometti et al, 2004). This strengthens the argument that loop 6 is accessible at the surface of 14-3-3s, since it must be available to kinases and that loop 6 remains accessible in complexes.…”
Section: -3-3 Loops Are Exposed When the Proteins Are Complexed Andsupporting
confidence: 55%
“…These data also suggest that these epitopes maintain the same structural conformation regardless of the client-binding state. Also of interest is the fact that GBC mAb 5D6 epitope in loop 6 is in the same region that has been recognized as the site of Ser phosphorylation in mammalian 14-3-3s (Woodcock et al, 2003) and potential Tyr phosphorylation in plant 14-3-3s (Giacometti et al, 2004). This strengthens the argument that loop 6 is accessible at the surface of 14-3-3s, since it must be available to kinases and that loop 6 remains accessible in complexes.…”
Section: -3-3 Loops Are Exposed When the Proteins Are Complexed Andsupporting
confidence: 55%
“…Most studies of the role of 14-3-3 in cellular regulation have focused on changes in target protein phosphorylation as the initial regulatory event; however, 14-3-3 proteins have been shown to be phosphorylated in animal systems (37,38) and in plants (39)(40)(41). Phosphorylation of 14-3-3 is another way in which these proteins are regulated (29), and in animal systems, a few kinases reportedly phosphorylate 14-3-3.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al (41) found that the 14-3-3 was phosphorylated at a Ser residue by plant extracts. The maize GF14-6 (14-3-3) was phosphorylated at Tyr-137 by insulin-like growth factor receptor 1 in vitro (40). The specific kinases that phosphorylate plant non-14-3-3 have not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations